Development of the Information System Program for Data Management among Patients with Cerebrovascular Diseases Hod Hospital, Chiang Mai Province - Thammakhun, Woranistha; Boonchieng, Waraporn; Thongprachum, Aksara; Boonchieng, Ekkarat (Journal of Nursing and Public Health Research, 2021)
The objectives of this research and development were to develop and to evaluate the effectiveness of the information system program for data management of patients with cerebrovascular diseases. There were three phases in the research procedure: the situation analysis phase, the operational phase, and the evaluation phase. These phases were evaluated using the System Development Life Cycle (SDLC). Participants were recruited by purposive sampling. Five participants were recruited for the situation analysis and the operational phases. Six participants were recruited for the evaluation phase. The research instruments were a structured interview and questionnaires about the efficiency and effectiveness of the program. Data were analyzed using descriptive statistics. The results from the situation analysis phase established that follow up contact guidelines regarding when to initiate and when to terminate post discharge contact with cerebrovascular patients were established. The follow up process was based on patient symptom severity. Patient care management was negatively affected by problems in sharing patient information due to incomplete, unclear, or missing important data via application line, messenger, or Facebook. This research showed that there were four steps in using the Information System Program: 1) accessing to the system, 2) displaying patient information, 3) receiving home care information, and 4) reporting the outcomes. The results from the evaluation phase indicated that the program was user friendly highly accessible and useful because it reduces the time to transfer information by linking the patient database to provide accurate and complete patient information.